Observational study of alternative therapies among paediatric emergency department patients. (28th February 2017) - Ding, Juen‐Li; Taylor, David McD; Lee, Marina; Johnson, Olivia G; Ashok, Aadith; Griffiths, Meg; Simma, Leopold; Craig, Simon S; Cheek, John A; Babl, Franz E
Abstract : Objective: While complementary medicine use among ED paediatric patients is common, the use of alternative therapies (ATs; physical or spiritual therapies) is unknown. We aimed to determine the 12 month period prevalence and nature of AT use among paediatric patients and parent perceptions of AT use. Methods: We undertook a cross‐sectional survey of a convenience sample of parents of paediatric patients in three EDs in metropolitan Melbourne, Australia (January–June, 2015). Parents were invited to complete a validated, anonymous, self‐administered questionnaire. The main outcomes were AT use by the patient and parent perceptions of ATs. Results: A total of 806 parents were enrolled. In the previous 12 months, 393 (48.8%) patients had received at least one AT. There were no gender or ethnicity differences between AT users and non‐users. AT use was more common among older patients ( P < 0.05). Patients with chronic illness tended to use more ATs ( P = 0.12). A total of 1091 courses of 43 different ATs had been provided. The most common were massage (16% of patients), chiropractic therapy (9.8%), relaxation (7.2%), meditation (6.2%) and aromatherapy (6.1%). ATs were generally used for musculoskeletal problems, health maintenance, stress and anxiety. Parents who arranged the ATs were significantly more likely to report that ATs are safe, prevent and treat illness, assist prescription medicines and offer a more holistic approach to healthcare ( P < 0.001). Conclusion: AT use is common among paediatric ED patients. Parents who arrange AT have differing perceptions of AT usefulness and safety from those who do not.